2005
DOI: 10.1074/jbc.m504303200
|View full text |Cite
|
Sign up to set email alerts
|

Potent Mechanism-based Inhibitors for Matrix Metalloproteinases

Abstract: Matrix metalloproteinases (MMPs) are zinc-dependent endopeptidases that play important roles in physiological and pathological conditions. Both gelatinases (MMP-2 and -9) and membranetype 1 MMP (MMP-14) are important targets for inhibition, since their roles in various diseases, including cancer, have been well established. We describe herein a set of mechanism-based inhibitors that show high selectivity to gelatinases and MMP-14 (inhibitor 3) and to only MMP-2 (inhibitors 5 and 7). These molecules bind to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
123
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 24 publications
2
123
0
2
Order By: Relevance
“…In these approaches, a bipronged effect of the respective inhibitor could be observed, namely inhibition of the metastatic potential, as well as inhibition of metastatic foci outgrowth (26). Application of synthetic inhibitors did not allow analysis of whether host-derived or tumor cell -derived gelatinases are important for metastasis nor did it elucidate distinct functions of the two gelatinases (24). To date, distinction of the respective functions of MMP-2 and MMP-9 in metastasis could therefore only be investigated preferably in gene deficiency models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these approaches, a bipronged effect of the respective inhibitor could be observed, namely inhibition of the metastatic potential, as well as inhibition of metastatic foci outgrowth (26). Application of synthetic inhibitors did not allow analysis of whether host-derived or tumor cell -derived gelatinases are important for metastasis nor did it elucidate distinct functions of the two gelatinases (24). To date, distinction of the respective functions of MMP-2 and MMP-9 in metastasis could therefore only be investigated preferably in gene deficiency models.…”
Section: Introductionmentioning
confidence: 99%
“…The greatest progress has been made when inhibitors were synthesized which were relatively specific for gelatinases (22) or even displayed mechanism-based binding to gelatinases (23,24). Indeed, these gelatinase-specific inhibitors were efficient in inhibiting aggressive metastasis in the well-established syngeneic and immunocompetent L-CI.5s lymphoma liver metastasis model (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the importance of MMP dysregulation in cancer development, identification and evaluation of MMP inhibitors as cancer chemotherapeutic agents are currently active areas of investigation [18][19][20]. Further, the use of MMP inhibitors in a cancer prevention ("chemoprevention") protocol is appealing due to the importance of basement membrane invasion in transformation of premalignant lesions, e.g., progression of oral epithelial dysplasia to HNSCC.…”
mentioning
confidence: 99%
“…Okamoto et al determined that glutathione (GSH), but not N-acetylcysteine (NAC), complexed with MMP-9's auto-inhibitory domain [13]. Other investigations by Albini et al demonstrated that introduction of NAC to conditioned medium obtained from cultured Kaposi sarcoma cells inhibited MMP-2 and MMP-9 gelatinase activity and that treatment of cultured Kaposi sarcoma cells with NAC significantly suppressed tumor cell invasion [17].Because of the importance of MMP dysregulation in cancer development, identification and evaluation of MMP inhibitors as cancer chemotherapeutic agents are currently active areas of investigation [18][19][20]. Further, the use of MMP inhibitors in a cancer prevention ("chemoprevention") protocol is appealing due to the importance of basement membrane invasion in transformation of premalignant lesions, e.g., progression of oral epithelial dysplasia to HNSCC.…”
mentioning
confidence: 99%
“…18 We also investigated the type of inhibition that was observed. As reported earlier in our mechanistic studies of the thiirane-type gelatinase inhibitors, slow-binding behavior is a hallmark of the mechanism of action of this type of inhibitors.…”
mentioning
confidence: 99%